TINJAUAN HUKUM TERHADAP KETERBUKAAN INFORMASI PEMERINTAH DAERAH DALAM PERSPEKTIF HUKUM PIDANA - Asmongin, Bharata Prabowo; Bunga, Marten; Tumuhulawa, Arifin (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2025)
This study examines public information disclosure by local governments from a criminal law perspective, focusing on weaknesses in the formulation of criminal offenses and the effectiveness of law enforcement. Based on the lex specialis derogat lex generalis principle, Law No. 14 of 2008 on Public Information Disclosure (UU PID) as a special regulation has not specifically formulated criminal offenses, particularly regarding the criminal liability of public bodies or corporations. Existing criminal sanctions, such as a maximum prison sentence of one year or fines, are deemed insufficient to provide an optimal deterrent effect. The dispute resolution mechanism through the Information Commission is procedurally effective but faces implementation challenges. The process begins with mediation and proceeds to adjudication if mediation fails. However, low legal understanding among public bodies, weak sanction enforcement, and inadequate oversight of decision implementation remain significant obstacles.This study recommends strengthening regulations through clearer formulation of criminal offenses, establishing criminal liability for public bodies, and enhancing the effectiveness of sanctions. Additionally, it is necessary to improve the capacity of law enforcement officers and public bodies in understanding and implementing the UU PID. Thus, public information disclosure in local governments can be carried out more effectively, accountably, and transparently.